Targeting the Sphingosine 1-Phosphate Axis as a Therapeutic Strategy in Krabbe's Disease: A Pre-Clinical Study. - BECHET, SIBYLLE (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2020)
Krabbe's disease (KD, globoid cell leukodystrophy) is a rare infantile neurodegenerative disorder, caused by the defective gene galc encoding the lysosomal hydrolase galactosylceramidase (GALC). A subsequent decreased enzymatic activity leads to the accumulation of the toxic metabolite galactosylsphingosine (psychosine). Supra-physiological levels of psychosine aggregates, in turn, cause profound demyelination and severe loss of oligodendrocytes, usually accompanied by neuroinflammation. Currently clinical practice lacks a curative treatment and is mostly directed towards symptomatic relief. Recent findings highlight the sphingosine 1-phosphate (S1P) axis as a therapeutic target in multiple sclerosis. Our lab has previously shown that S1P receptor modulation with fingolimod and siponimod, two S1P receptor agonists, attenuate psychosine-induced cell death of human astrocytes in vitro and demyelination in mouse organotypic cerebellar slice cultures. Together, this data prompted the current preclinical studies investigating the effects of fingolimod in both adolescent and neonatal twitcher mice, the murine model of KD (Results, chapter 3 and 4). We additionally examined the relative impact of S1PR1, S1PR3 and S1PR5 subtypes by administering the selective S1PR1/5 agonist, siponimod (Results, chapter 5). Using this S1PR3 sparing compound we investigated the role and importance of S1PR3 in the context of demyelination and inflammation in twitcher mice. Here, we found that fingolimod, but not siponimod, administered at postnatal day (PND) 21 resulted in improved myelination in twitcher mice (Results, chapter 3 and 5). Such results raise the hypothesis that remyelination may be, in part, linked to S1PR3 activation. Interestingly, both compounds, however, were able to alter microglia and astrocytes activation, thus suggesting that S1PR1/5 was sufficient to modulate the activation state of these cells. Neonatal administration of fingolimod was able to reduce myelin debris, dampen microglial activation, without, however, increasing myelin markers (Results, chapter 4). Behaviourally, fingolimod was able to modestly enhance lifespan, with sporadic phenotypic improvements, when administered at PND5 and PND21, whereas siponimod did not result in a significant increase in lifespan. Although both compounds were able to provide partial efficacy within the CNS, they failed to improve peripheral systems (sciatic nerve, kidney, spleen). Such findings emphasise the importance of combination therapies targeting both the CNS as well as peripheral systems in a multimodal illness such as KD.
APPROVED
Keywords: Krabbe's Disease; Globoid Cell Leukodystrophy; Fingolimod, FTY720; Demyelination; Neuroinflammation